English Interjections and Their Translation in The Subtitles of My Little Pony Movie - Dinata, I Kadek Aditya; Jayantini , I Gusti Agung Sri Rwa; Juniartha , I Wayan (Journal of Language and Applied Linguistics, 2023)
The study focused on identifying the functions of interjections and translation strategies of interjections were found in the subtitle of My Little Pony movie. The data were collected by observation method and analyzed in descriptive qualitative method. The research used two theories, namely the categories of interjections proposed by Ameka (1992) and translation strategies of interjections proposed by Cuenca (2006). It is found that four functions of interjections applied, there are, 26 data of emotive interjection, 2 data of cognitive interjection, 14 data of conative interjection, and 7 data of phatic interjection. Furthermore, there were five translation strategies of interjections found in this research. There were 28 data of literal translation, 3 data of translation by using an interjection with different form but expressing the same meaning, 4 data of translation by an interjection with different meaning, 12 data of omission strategies, and 2 data of addition strategies. Literal translation was the most frequent strategy applied because the translator transferred the message from the source language into target language with the same meaning or expression and did not change the form of interjection.